Enhanced WSN Cloud Security Based on Double Linked Hash Blockchain Security using Prime Padding Rivest Cipher Key policy - Ramani, R.; Prasad, D. Rajendra; Kumar, CH. Mohan Sai; Karthikeyan, T.; Choubey, Shruti Bhargava; Rajasekar, S. S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing and wireless sensor Network are hands on technology in recent advanced developments in healthcare sectors. Also the security is a critical concern for healthcare because of sensitive information handling is so difficult due to cryptography failures leads, key leakage problems, data breaches, integrity proofing failures and soon. The blockchain make a revolution in heath security failures to make higher end communication security. To consider this problems, propose a balck chain security based on Double Linked Hash Blocks (DLHB) using Prime Padding Rivest Cipher Key Generation policy to improve the security to protect the sensitive information. The block chain creates a Double Linked Hash Blocks (DLHB) and the collected data’s are parsed to each block with hash index. The block chain creates Shuffle Structure Chain Link (SSCL) to make chain link policy to decentralized communication with Master Node Aggregation (MNA).The Blocks get encrypted with Advanced Encryption Standard (AES) and data blocks are shifted with spiral rotation. The AES model generates the block cipher key which act as communication transmission key. The Prime Padding Rivest Cipher Key Generation (PP-RCKG) policy is used to create a secret key for encrypted blocks. Then the block are circulated into chain link to make communication and key get verified by master node authentication policy to safely handover the data. The proposed system improve the security as well in security verification and validation performance, integrity proofing accuracy compared to the previous system